2022
DOI: 10.1001/jamanetworkopen.2022.41291
|View full text |Cite
|
Sign up to set email alerts
|

Association of Noncontrast Computed Tomography and Perfusion Modalities With Outcomes in Patients Undergoing Late-Window Stroke Thrombectomy

Abstract: ImportanceThere is substantial controversy with regards to the adequacy and use of noncontrast head computed tomography (NCCT) for late-window acute ischemic stroke in selecting candidates for mechanical thrombectomy.ObjectiveTo assess clinical outcomes of patients with acute ischemic stroke presenting in the late window who underwent mechanical thrombectomy stratified by NCCT admission in comparison with selection by CT perfusion (CTP) and diffusion-weighted imaging (DWI).Design, Setting, and ParticipantsIn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…There were comparable rates of sICH between the 2 groups (OR 1.09, 95% CI 0.58–2.04; p = 0.80); however, there was significant heterogeneity noted among studies ( I 2 = 67%, p = 0.017) (Figure 4). On removal of the outlier study, 5 the results still yielded comparable rates of sICH between the 2 groups (OR 0.76, 95% CI 0.52–1.10; p = 0.15) (eFigures 3 and 4, links.lww.com/WNL/C725).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…There were comparable rates of sICH between the 2 groups (OR 1.09, 95% CI 0.58–2.04; p = 0.80); however, there was significant heterogeneity noted among studies ( I 2 = 67%, p = 0.017) (Figure 4). On removal of the outlier study, 5 the results still yielded comparable rates of sICH between the 2 groups (OR 0.76, 95% CI 0.52–1.10; p = 0.15) (eFigures 3 and 4, links.lww.com/WNL/C725).…”
Section: Resultsmentioning
confidence: 89%
“…5 Dekker et al reported data from the Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands (MR CLEAN) database, a multicenter, prospectively maintained registry. ASPECTS were comparable between CTP-selected patients (median 7, IQR 7 Nguyen et al 6 Nogueira et al 4 Porto et al 5 Dekker et al 8 Comparison and NCCT-selected patients (median 9, IQR 7-10). Patients with anterior circulation large vessel (intracranial carotid artery, middle cerebral artery M1/M2 segment, or anterior cerebral artery A1/A2 segment) occlusion and TLSW or symptom onset to arterial puncture of beyond 6.5 hours were included.…”
Section: Search and Screening Resultsmentioning
confidence: 99%
See 3 more Smart Citations